Building Multicultural Personality Through Religious Moderation In Early Childhood Education: Case Study in Ponorogo - Puspitasari, Ratna Nila; Soraya, Siti Zazak (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
Integrating religious moderation into early childhood education is an important approach to forming multicultural personalities in children. This research explores the application of religious moderation in early childhood education and its impact on children's growth and development. This research involved using a qualitative case study method, which involved six teachers from three kindergartens in Ponorogo. Data collection was carried out through interviews, observation, and document analysis, with data analysis following an interactive model that included data collection, condensation, display, and verification. The findings reveal that religious moderation forms a multicultural personality using culture-based activities that can develop cultural empathy and accommodation towards local culture, routine ceremonies and those included in learning activities develop open-mindedness and national commitment, religious activities develop flexibility and tolerance, and fair treatment of teachers and principals. schools and students develop emotional stability and anti-violence, and social activities develop social initiative and tolerance. Although there are challenges, such as differences in religious viewpoints and difficulties in integrating national and local curricula, the benefits include reducing excessive religious fanaticism and encouraging empathy and tolerance.Â